UTILIZING THE DUOLINGO APPLICATION FOR SELF-DIRECTED ENGLISH VOCABULARY LEARNING AT MTS MUHAMMADIYAH 1 SAMARINDA - Raadhiyah, Azkiya Firdausi ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2025)
This research examines the utilization of the Duolingo application for self-directed learning of English vocabulary at MTS Muhammadiyah 1 Samarinda. English as an International Language and the utilization of digital platforms as learning media is very effective and fun. Duolingo was identified as an effective and popular platform for language learning, which utilizes a gamification approach and enables self-directed learning. This study used a descriptive method with a qualitative approach, involving 10 grade 9 students of MTS Muhammadiyah 1 Samarinda who were selected through purposive sampling based on their experience using Duolingo. Data collection was conducted through direct interviews with 7 questions. The results showed that Duolingo makes it easier for users to learn English vocabulary, with feedback and repetition features that reinforce understanding. In addition, ease of use makes Duolingo accessible and usable by people of all ages. Factors such as attractive appearance, flexibility, clear explanation of material, repetition of material, gamification approach, and various language options make this application attractive to users.